1999
DOI: 10.1093/ps/78.5.714
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane mimics the pulmonary but not systemic vascular responses to bolus HCl injections in broiler chickens

Abstract: Bolus i.v. injections of 1.2 N HCl elicit a rapid but transient pulmonary vasoconstriction in broiler chickens. In mammals, the pulmonary vasoconstrictive response to bolus acid injection depends on increased synthesis of thromboxane A2; however, the vascular responsiveness of domestic fowl to thromboxane previously had not been evaluated. In the present study, we tested the hypothesis that, if HCl triggers pulmonary vasoconstriction by stimulating thromboxane A2 synthesis in broilers, then bolus i.v. injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The U44069 (Sigma Chemical Co.) was diluted to 1 mM in 2.5% mannitol, and was injected as a 0.05-to 0.1-mL i.v. bolus as described previously (Wideman et al, 1999Chapman and Wideman, 2006b). Previously we demonstrated that neither i.v.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The U44069 (Sigma Chemical Co.) was diluted to 1 mM in 2.5% mannitol, and was injected as a 0.05-to 0.1-mL i.v. bolus as described previously (Wideman et al, 1999Chapman and Wideman, 2006b). Previously we demonstrated that neither i.v.…”
Section: Methodsmentioning
confidence: 99%
“…The mammalian PH response to LPS appears to be mediated primarily by ET-1 and TxA 2 (Morel et al, 1989;Longworth et al, 1994;Faltin et al, 1996;Snapper et al, 1998;Wanecek et al, 2000). Thromboxane A 2 , ET-1, and 5-HT are known to be potent pulmonary vasoconstrictors in chickens (Wideman et al, 1998(Wideman et al, , 1999Martinez-Lemus et al, 1999Wideman, 2002, 2006a,b;Villamor et al, 2002;Yang et al, 2005). Recent experiments demonstrated that the major peak of broilers' PAP response to LPS cannot be attributed to 5-HT (Chapman and Wideman, 2006c;Chapman et al, 2008); therefore, in the present study we assessed the potential role of arachidonic acid (AA) derivatives such as TxA 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous AA infusions trigger rapid increases in the pulmonary vascular resistance and pulmonary arterial pressure in broilers, and these responses are blocked by inhibiting cyclooxygenases (Wideman et al, 2005a(Wideman et al, , 2009. Thromboxane A 2 , whether administered intravenously as the TxA 2 mimetic U44069 or produced by activated thrombocytes, consistently causes pulmonary vasoconstriction and pulmonary hypertension in broilers (Wideman et al, 1996b(Wideman et al, , 1998a(Wideman et al, , 1999a(Wideman et al, , 2005a(Wideman et al, , 2009Villamor et al, 2002;Chapman and Wideman, 2006b). The precise contribution of TxA 2 to the progression of pulmonary hypertension in PAHsusceptible broilers remains to be determined.…”
Section: Mediators Of Pulmonary Vasoconstrictionmentioning
confidence: 99%
“…Prostanoids are produced in chicken blood vessels and participate in the regulation of vascular tone (Chand and Eyre 1976;Claeys et al 1981;Wideman et al 1999). However, we have observed that in the chicken DA COX inhibitors did not produce signiWcant contractile eVects (Agren et al 2007) and did not aVect endothelium-dependent relaxation (Agren et al 2008), suggesting that locally produced PGs are not important mediators in the control of chicken ductal tone.…”
Section: Introductionmentioning
confidence: 99%